A 7/7 NHS: what price equity?. (26th January 2016) - Appleby, John
Abstract : What are we willing to forgo to rectify unequal outcomes between weekend and weekday admissions? And, harder still, can the NHS justify spending the money to iron out these differences, asks John Appleby